EFEKTIVITAS PENGGUNAAN KOMIK DIGITAL BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR IPAS KELAS III SDN 1 KUWUKAN: EFEKTIVITAS PENGGUNAAN KOMIK DIGITAL BERBASIS KEARIFAN LOKAL TERHADAP HASIL BELAJAR IPAS KELAS III SDN 1 KUWUKAN - Ayu Paramastuti; Imaniar Purbasari; Khamdun (STKIP Subang, 2025)
This study investigates the effectiveness of local wisdom-based digital comics on Natural and Social Sciences (IPAS) learning outcomes among third-grade students at SDN 1 Kuwukan. The research employed a quasi-experimental design with one group pretest-posttest design involving 15 students as subjects. The digital comic media integrated local wisdom elements from Kuwukan Village, including Sewu Kupat Tradition, Barongan Art, village environmental conditions, gotong royong values, and traditional kupat food. Data collection utilized validated and reliable learning outcome tests with expert validation showing 95.45% validity in the